Preparing a Journal to be Accredited Nationally by Sinta - Wibisono, M. Yusuf; Rahman, Mohammad Taufiq (FISIP UIN SGD Bandung, 2024)
Journals, which represent the most recent findings from a particular scientific expertise, are the most visible scientific output for the scientific community. This specialization is also what makes a journal visible to indexers like Sinta. In this case, the Religious Studies Doctoral Study Program at State Islamic University (UIN) of Sunan Gunung Djati (SGD) of Bandung has the Hanifiya Journal following Sinta's standards. Thus, to support improving the quality of management, preparation activities for the Accredited Journal of Sinta are needed. Journal management has unique characteristics for its scientific field. With the unique characteristics of journal governance, the study program-based scientific community is expected to be able to obtain appropriate and detailed knowledge and services regarding study program science. This program of Journal upgrades four essential elements: articles, reviewing, editorial and publication. The targets aimed at the management of this journal are primarily lecturers and study program students, plus journal managers and the Postgraduate Administration of the University. Resource people with appropriate knowledge of the Sinta journal were invited to participate in this project. Additionally, it is customary for visiting writers from various universities to be invited to contribute to the Hanifiya Journal. As a result, each writer and management receives support and ongoing guidance in order to prepare them for Sinta's national journal certification in Indonesia.